Effect of adjuvant chemotherapy after pulmonary metastasectomy on the prognosis of colorectal cancer - Shiomi, Kazu (Ann Med Surg (Lond), 2017)
BACKGROUND: Adjuvant chemotherapy after resection of colorectal cancer (CRC) lung metastases may reduce recurrences and improve survival. We investigated the effects of adjuvant chemotherapy after curative resection of lung CRC metastases on prognosis. METHODS: We retrospectively reviewed records of our patients undergoing pulmonary metastasectomy from CRC between January 2000–March 2014. Data were analyzed with Kaplan-Meier survival analysis and Cox proportional hazards models. RESULTS: One-hundred (56 men; median age, 66 years) of 128 consecutive patients who underwent complete resection for first lung colorectal metastases were analyzed. Postoperative 5-year rates of overall survival (OS) and relapse-free survival (RFS) were 76% and 41%, respectively. Adjuvant chemotherapy strongly affected RFS and OS by multivariable analysis compared to surgery alone (RFS: HR, 0.49; 95% CI, 0.27–0.88; P = 0.016 and OS: HR, 0.35; 95% CI, 0.14–0.81; P = 0.014). Similar effects of adjuvant chemotherapy occurred in subgroups respectively classified according to number of lung metastases and preoperative serum carcinoembryonic antigen (CEA) level. CONCLUSIONS: Adjuvant chemotherapy after curative resection of lung metastases might strongly affect the prognosis of metastatic CRC patients. Even patients with single metastatic lesions and normal preoperative CEA level appeared to receive benefits from such chemotherapy. Narrowing of suitable candidates by predicting the effects of systemic chemotherapy and prospective randomized studies are needed.